Health-related impacts of climate change and air pollution on older adult, child, and adolescent immigrants and refugees globally: a scoping review. - Sidney, Brooke T.; Chandras, Shubham; Campbell, Sandra M.; Salma, Jordana; Yamamoto, Shelby S. (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Aim: Climate change and air pollution exposures are global issues impacting human health. This scoping review aims to synthesize evidence on the health-related impacts of climate change and air pollution exposures on immigrant and refugee populations younger than 18 and 65 years and older, and to determine if the impacts are influenced by age, immigrant category, gender, and/or geographical location. Subject and methods: Databases were searched from inception to July 2022 and included PROSPERO, OVID Medline, OVID EMBASE, Wiley Cochrane Library (CDSR and Central), Proquest Dissertations and Theses Global and SCOPUS. All time frames, languages, and geographic locations were included. Types of evidence sources included were reviews (e.g. scoping, systematic, clinical), books, and descriptive (e.g., ecological) and analytical (e.g. case–control, cross-sectional and cohort) studies. Results: Three studies fit the criteria. All used secondary data sources, different study designs and analysis approaches and defined immigrants, refugees, and exposures differently. Only climate change exposures (excessive temperatures) were explored, with mortality and respiratory syncytial virus outcomes. Two articles found that foreign-born and non-US citizens 65 years and older were similarly or less susceptible compared to native-born, but younger individuals were more susceptible. The other found that higher temperatures were associated with higher respiratory syncytial virus incidence in refugee children younger than 5 years old. If stratification was done, only sex, age, race, ethnicity, and place of birth were examined. Conclusions: Immigrants and refugees are understudied in the literature and often excluded. Additional research is needed to determine other exposures and health outcomes for immigrant and refugee populations.